2021
DOI: 10.1038/s41598-021-88340-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutricosmetic effects of Asparagus officinalis: a potent matrix metalloproteinase-1 inhibitor

Abstract: This study aimed to investigate the nutricosmetic effect of Asparagus officinalis extracts. The tip and spear of A. officinalis were successively extracted with 95% ethanol. The rutin, phenolic, and flavonoid contents of A. officinalis extracts were investigated. The antioxidant activities were determined by 2,2-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) and a ferric reducing antioxidant power assay. Matrix metalloproteinase-1 (MMP-1), elastase, and hyaluronidase inhibition were determined by in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Since A. officinalis and A. thaliana were exposed to different environments during the evolution process, the number of NAC genes in their subgroups became different as NAC genes differentiated. Gene duplication is closely related to the evolution of genome size, the origin of new genes, species differentiation, and the ability of gene anti-mutation [ 51 , 77 ]. The collinearity analysis in our study showed that there were three pairs of tandem duplication and five pairs of segmental duplication events in the A. officinalis NAC gene family, and this might play an important role in the NAC family expansion in garden asparagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since A. officinalis and A. thaliana were exposed to different environments during the evolution process, the number of NAC genes in their subgroups became different as NAC genes differentiated. Gene duplication is closely related to the evolution of genome size, the origin of new genes, species differentiation, and the ability of gene anti-mutation [ 51 , 77 ]. The collinearity analysis in our study showed that there were three pairs of tandem duplication and five pairs of segmental duplication events in the A. officinalis NAC gene family, and this might play an important role in the NAC family expansion in garden asparagus.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide asparagus production reached 8.45 million metric tons in 2020 [ 50 ]. Additionally, its materials have also been used for centuries as herbal medicine because it is rich in amino acids, folic acid, ascorbic acid, phenols, saponins, dietary fiber, anthocyanins, and so on [ 51 ]. Soil salinization is one of the main limiting factors of agricultural production which seriously affects the growth and development of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Different preparations (tip and spear and steam extract) of asparagus ( Asparagus officinalis L.) were studied by Sriyab et al [ 146 ] and Shirato et al [ 147 ] for nutricosmetic effects, especially the anti-aging potential. Sriyab et al [ 146 ] aimed to evaluate the nutricosmetic effects of A. officinalis extracts. The tips and spears of A. officinalis were extracted with 95% ethanol.…”
Section: Anti-aging Effects Of Vegetablesmentioning
confidence: 99%
“…Asparagus ( Asparagus officinalis L.), a perennial herb and stem vegetable native to the eastern Mediterranean and Asia Minor, is now globally cultivated in more than 60 countries (Guo et al ., 2020). The edible part of the asparagus, commonly called as stalks, corresponds to approximately 50% of its total and other 50% discarded as by‐products in the form of hard‐stems, roots, and leaves during processing (Sriyab et al ., 2021). For this reason, many national and international organisations are enforcing sustainable utilisation of waste generated from fruits and vegetables through technological developments.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many national and international organisations are enforcing sustainable utilisation of waste generated from fruits and vegetables through technological developments. In recent years, asparagus hard‐stem has attracted the scientific attention due to the presence of similar bioactive compounds as in the main products, such as phenolic compounds, saponins, and dietary fibre (Chitrakar et al ., 2019; Romani et al ., 2021; Sriyab et al ., 2021). Fresh asparagus hard‐stems contain more than 91% water, and the remaining content is composed of protein (15.90%), crude fat (1%), crude fibre (1.80%), total sugars (5.70%), and reducing sugars (5.50%) (Guan et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%